Exposure to phthalate esters in Japanese females in Kyoto, Japan from 1993 to 2016: Temporal trends and associated health risks. (July 2022) - Lyu, Zhaoqing; Harada, Kouji H.; Kim, Sungmin; Fujitani, Tomoko; Cao, Yang; Hitomi, Toshiaki; Fujii, Yukiko; Kho, Younglim; Choi, Kyungho
Graphical abstract: Proportion of the phthalates that produced the maximum hazard quotient in 1993–2016. Abstract: Phthalates are used as plasticizers in many products used in daily life worldwide. Due to industrial and economic developments, exposure among general population to phthalates may vary geographically and temporally. However, studies are lacking for investigating temporal changes in phthalate exposure in the Japanese population. In the present study, the temporal trends in exposure to various phthalates were assessed among a group of Japanese adult female population over 1993–2016 and derived associated risks. For this purpose, urine samples of healthy Japanese females in Kyoto, Japan (N = 132) collected in 1993, 2000, 2003, 2009, 2011, and 2016, were employed and measured for the concentrations of 18 phthalate metabolites. Over this period, the detection rates of mono(3-carboxypropyl) phthalate (MCPP) and monoisobutyl phthalate (MiBP) decreased, and the geometric means of the urinary concentrations of mono(2-ethyl-5-carboxypentyl) phthalate (MECPP), and mono(2-ethyl-5-oxohexyl) phthalate (MEOHP) showed a significant decreasing trend. Cumulative risk due to exposure to dibutyl phthalate (DBP), diisobutyl phthalate (DiBP), butyl benzyl phthalate (BBP), and di-2-ethylhexyl phthalate (DEHP) showed a dramatic decrease only between 1993 and 2000. The maximum hazard quotient (HQM ) was attributed to DEHP in most subjects regardless of sampling year. This study showed the temporal trend of the exposure of Japanese females to several phthalate esters over two decades. As of the late 2010's, DEHP was still the predominant component of phthalate ester exposure in the population. The HI value, however, indicates that direct risk due to phthalate exposure was unlikely among the studied population.